Analysis of the Impact of Information and Communication Technology on Nigeria Bottling Company's Organisational Performance: Array - Onikoyi, Idris Adegboyega; Adebayo, Aderemi Olalere; Adenuga, Johnson Oladimeji; Babalola, Haorayau Bolaji; Lamidi, Wasiu Adebayo (Acta Universitatis Danubius. Œconomica, 2022)
Information and communication technology (ICT) has long been recognized as a critical component of any business's ability to maximize profit, ensure customer happiness, and reduce costs. The researcher, therefore, examine the analysis of the impact of ICT on Nigeria Bottling Company’s organisational performance. The study used a descriptive survey research design. Data was gathered from Nigeria Bottling Company employees in South West state using a standardized questionnaire. (NBC). The study's participants were 3,746 NBC employees. Because of the large population, Godden (2004) formula was utilized to determine the sample size of 385. The respondents' level of expertise of the research topic necessitated the utilization of a purposeful sampling technique. The choice was deliberate to optimize resources and to get reliable information. The data collected was analyzed using multiple regression and correlation analysis. The studies demonstrated that information and communications technology (ICT) had a substantial impact on NBC's organisational performance. Furthermore, with an R2 value of (0.743), internet access has a favorable impact on organisational performance, and factors statistically significant at the 95 percent confidence level and sig 0.000, there is a substantial association between cloud computing and organisational performance. Based on the findings, the study stated that there is adequate evidence to prove that ICT adoption has a substantial impact on NBC's organisational performance. Therefore, the researcher recommends that organisations should embrace internet access so as to have effective planning, execution and better communication in reaching its customers and beneficiaries